Fabrication and electroluminescence properties of alloyed CdS xSe1-xquantum dots-based LEDs - Nguyen, Huu Tuan; Chen, Shutang; Duong, Anh Tuan; Lee, Soonil (Semiconductor Science and Technology, 2022)
We report on the facile synthesis of alloyed CdS x Se1-x quantum dots (QDs) via a one-pot method using the simultaneous injection of Se and S source into a solution of the Cd precursor dissolved in a coordinating mixture of hexadecylamine and trioctylphosphine, during which the formation of CdS x Se1-x nanocrystals was controlled by growth time at a temperature of 260 C. In particular, the emission peak and full width at half maximum of the photoluminescence (PL) of alloyed CdS x Se1-x QDs were tunable in the range of 588-604 nm and 36-38 nm, respectively, with a PL quantum yield of up to 55% by a reaction time of 60 min. Importantly, the structural advantage of alloyed CdS x Se1-x QDs-based light emitting devices have been fabricated and their electroluminescence properties characterized. A good performance device with a maximum luminance and luminous efficiency of 761 cd m-2 and 0.82 cd A-1, respectively, was obtained.
Keywords: Alloyed cdsxse1-x quantum dot; Electroluminescence properties; Emission peaks; Facile synthesis; Full widths at half maximums; Growth time; Hexadecylamine; One-pot method; Simultaneous injections; Trioctylphosphines; alloyed CdSxSe1-x QDs; electroluminescence; hexadecylamine; photoluminescence; QD-LEDs; trioctylphosphine